2022
DOI: 10.3389/fvets.2022.993773
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key pathways and genes that regulate cashmere development in cashmere goats mediated by exogenous melatonin

Abstract: The growth of secondary hair follicles in cashmere goats follows a seasonal cycle. Melatonin can regulate the cycle of cashmere growth. In this study, melatonin was implanted into live cashmere goats. After skin samples were collected, transcriptome sequencing and histological section observation were performed, and weighted gene co-expression network analysis (WGCNA) was used to identify key genes and establish an interaction network. A total of 14 co-expression modules were defined by WGCNA, and combined wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Melatonin regulates both reproduction and alopecia in humans ( 12 , 45 ). Promotion of secondary hair follicle growth has also been obtained in studies on goats ( 13 ). Melatonin plays a promotional role during in vitro maturation of goat and human oocytes ( 14 , 17 ).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Melatonin regulates both reproduction and alopecia in humans ( 12 , 45 ). Promotion of secondary hair follicle growth has also been obtained in studies on goats ( 13 ). Melatonin plays a promotional role during in vitro maturation of goat and human oocytes ( 14 , 17 ).…”
Section: Discussionmentioning
confidence: 91%
“…Melatonin promotes the expression of MTNR1A ( melatonin receptor 1A ) in human and rex rabbit hair follicles ( 42 , 43 ) and also enhances the expression of goat Wnt10b and beta-catenin ( 26 ). The signaling pathways involved in the regulation of hair follicle growth by melatonin are the PI3K/AKT signaling ( 43 ), Hippo, TGF-beta, MAPK signaling ( 13 ), and AKT/GSK3beta/beta-catenin signaling pathways ( 44 ). The results of the present study suggest that the MAPK signaling pathway is also at the forefront of KEGG enrichment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been 64 lncRNAs with differential expression during melatonin-mediated secondary hair follicle growth in Shaanbei cashmere goats, and lncRNAs TCONS_00255106 and TCONS_00206163 may regulate COL4A2 and THBS2 expression in a cisacting manner 4 . After melatonin implantation in live Inner Mongolian cashmere goats, six pivotal genes correlated with cashmere growth (i.e., PDGFRA, WNT5A, PPP2R1A, BMPR2, BMPR1A, and SMAD) have been identi ed through combinatorial differential gene expression analysis 5 . Existing research on melatonin-promoted cashmere growth has placed a major focus on the gene level 4 , whereas rare studies have reported that melatonin promotes the proliferation of cashmere skin broblasts by regulating noncoding RNAs.…”
Section: Introductionmentioning
confidence: 99%